Quantitative Evaluation of the Production of Ligninolytic Enzymes-Lignin Peroxidase and Manganese Peroxidase by P. Sajor Caju During Coir Pith Composting - Radhakrishnan, S.; Ravindranath, Anita Das; Hanosh, M. S.; Sarma, U. S.; Jayakumaran, Nair A. (International Coconut Community Journal, 2012)
Coir is the natural hard fruit fibre extracted from the exocarp of the coconut. The fibre has over 40 percent lignin and is spun into yarn and rope. Coir is used globally for manufacturing floor coverings as home furnishing. The Coir Industry enjoys the status as the largest cottage industry in Kerala giving employment to over a million people, of which 80 percent constitute women. Coir pith is a biomass residue generated during the extraction of coir fibre from coconut husk. Coir pith produced during coir fibre extraction is of environmental concern as its dumping on shore line and leaching of its constituents alter water quality and aquatic life. Management of coir pith is a major problem with all coir industrialists. Hillocks of coir pith accumulate in the vicinities of coir fibre extraction units in Kerala, Tamil Nadu, Andhra Pradesh, Karnataka, and Orissa. These agricultural wastes have traditionally been disposed by burning which resulted in various environmental problems. Therefore, composting is an alternate way to dispose coir pith and is of critical importance. Ligninolytic enzyme production during coir pith composting by Pleurotus sajor caju has been studied in detail. Pleurotus sajor caju produces oxidative enzymes which degrade lignin in the presence of urea as nitrogen source. Substitution of urea with vegetative sources has resulted in the vigorous growth of the mushroom which leads to decreased lignin content and C: N ratio in the biodegraded coir pith. Combination of Azolla and Soya hulls as biological supplements was observed to be the best substitute for lignin peroxidase and manganese peroxidase production. Activity of manganese peroxidase and lignin peroxidase was maximum on the twentieth day of fermentation of coir pith. The level of enzyme activity during biological composting using vegetative sources was compared with the conventional process using urea. The enzyme profile exhibited variation with change in substrate and duration of decomposition. The colonization of Pleurotus sajor caju by its utilization leads to biochemical changes in coir pith converting it into an ideal plant nutrient.